COVID-19 and Inequality in Asia : Breaking the Vicious Cycle. (IMF Working Papers; Working Paper ;, 2020)
The COVID-19 pandemic risks exacerbating inequality in Asia. High frequency labor surveys show that the pandemic is having particularly adverse effects on younger workers, women and people that are more vulnerable. Pandemics have been shown to increase inequalities. As a result, income inequality, which was already high and rising in Asia before the pandemic, is likely to rise further over the medium term, unless policies succeed in breaking this historical pattern. Many Asian governments have implemented significant fiscal policy measures to mitigate the pandemic's effect on the most vulnerable, with the impact depending on the initial coverage of safety nets, fiscal space, and degree of informality and digitalization. The paper includes model-based analysis which shows that policies targeted to where needs are greatest are effective in mitigating adverse distributional consequences and underpinning overall economic activity and virus containment.